Guitar technique in scenes from the wild west for guitar solo / Jadrye Jakiwa - Jakiwa, Jadrye (Faculty of Music, 2010)
This research is conducted to identify the technique in scenes from the Wild West for guitar solo by Gary Ryan. Three subjects have been selected to answer interview questions regarding their experiences and knowledge of Gary Ryan pieces The findings shows there are many ways or practice for the technique in scenes from the Wild West. This research will present two findings which to identify of playing in scenes from the Wild West and in identify way of developing a proper method of practicing for the playing technique of the repertoires.